2018
DOI: 10.1074/jbc.ra118.002611
|View full text |Cite
|
Sign up to set email alerts
|

Binding conformation and determinants of a single-chain peptide antagonist at the relaxin-3 receptor RXFP3

Abstract: The neuropeptide relaxin-3 and its receptor relaxin family peptide receptor-3 (RXFP3) play key roles in modulating behavior such as memory and learning, food intake, and reward seeking. A linear relaxin-3 antagonist (R3 B1-22R) based on a modified and truncated relaxin-3 B-chain was recently developed. R3 B1-22R is unstructured in solution; thus, the binding conformation and determinants of receptor binding are unclear. Here, we have designed, chemically synthesized, and pharmacologically characterized more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…The NMR structural analysis confirmed that the apamin scaffold does confer helical structure, but that the C-terminal part of the peptide after the last cysteine, which includes the key antagonist binding residue ArgB23, remains highly flexible. Again this is consistent with detailed structure activity analysis of R3 B1-22R, which suggest a degree of flexibility is a prerequisite for optimal binding (Haugaard-Kedström et al, 2018;Wong et al, 2018). The VhTI grafted antagonist was based on the first version of the VhTI agonist and retained the native Pro residue from VhTI instead of ArgB12.…”
Section: Assessment Of Affinity and Activity Of Peptide Analogs At Rxfp3supporting
confidence: 80%
See 4 more Smart Citations
“…The NMR structural analysis confirmed that the apamin scaffold does confer helical structure, but that the C-terminal part of the peptide after the last cysteine, which includes the key antagonist binding residue ArgB23, remains highly flexible. Again this is consistent with detailed structure activity analysis of R3 B1-22R, which suggest a degree of flexibility is a prerequisite for optimal binding (Haugaard-Kedström et al, 2018;Wong et al, 2018). The VhTI grafted antagonist was based on the first version of the VhTI agonist and retained the native Pro residue from VhTI instead of ArgB12.…”
Section: Assessment Of Affinity and Activity Of Peptide Analogs At Rxfp3supporting
confidence: 80%
“…The VhTI grafted antagonist was based on the first version of the VhTI agonist and retained the native Pro residue from VhTI instead of ArgB12. The relative importance of ArgB12 for binding to RXFP3 in antagonists is significantly less than in native relaxin-3 (Haugaard-Kedström et al, 2018;Wong et al, 2018), thus we did not anticipate this being detrimental to affinity. However, analog 10 showed very poor binding to RXFP3 (Table 2, Figure 6), which again is likely related to the positioning of the binding residues on the helical surface.…”
Section: Assessment Of Affinity and Activity Of Peptide Analogs At Rxfp3mentioning
confidence: 93%
See 3 more Smart Citations